Communication Patterns in Distant Relationship Couples Dating in Maintaining Commitment Through Whatsapp - Priti Hiltania Zebua; Dwi Kartikawati (IJESS International Journal of Education and Social Science, 2023)
This research is to examine how Long-Distance Relationship Communication Patterns in Maintaining Commitments Through Whatsapp Media in dating couples. The development of communication technology is not an obstacle in establishing long-distance relationships. Long Distance Relationship (LDR) is a pair of lovers who are in a relationship separated by distance and time. The people involved in the relationship will continue to feel the push and pull of conflicting desires in all parts of the life of the relationship. Long Distance Relationships (Long Distance Relationship) require an effective communication process in order to maintain harmonious relationships by using a communication tool in the form of a medium, namely WhatsApp. This research is based on the theory of Relational Dialectics and is supported by Computer Mediated Communication (CMC) theory, complemented by the concept of interpersonal communication theory and the foundation of interpersonal communication. The method used was qualitative with a phenomenological approach for 10 partner informants with criteria determined by the researcher. The results of this study indicate that communication patterns in long-distance relationships carried out by informants consist of separate balanced communication patterns, separate unbalanced communication patterns and balanced communication patterns. Also from this research, the five couples hope that the long-distance relationship that is being forged can progress to a more serious stage, namely marriage, looking for the best solution for each other, and learning to understand each other's partners.